Pyrene core-based self-assembled monomolecular layer organic semiconductor material and preparation method and application thereof

By using self-assembled single-layer organic semiconductor materials based on pyrene-core self-assembled single-layer organic semiconductor materials in perovskite solar cells, the problem of poor perovskite solution in PTAA material is solved, and more efficient hole transmission and higher photoelectric conversion efficiency are achieved .

CN119462742APending Publication Date: 2025-02-18HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411586594.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In existing perovskite solar cells, the perovskite solution of the hole transport material PTAA has poor wetting properties, resulting in poor film formation quality and high interfacial defect density, limiting device performance improvement and commercial applications.

Method used

Using self-assembled single-layer (SAMs) organic semiconductor materials based on pyrene nuclei, phosphoric acid is used as the anchor group and benzene ring is used as the connecting unit. The pyrene has a large conjugated planar structure, which promotes intermolecular interaction and self-assembly, A dense hole transport layer is formed.

Benefits of technology

The hole mobility and extraction capacity are improved, the hole transmission performance is enhanced, and the photoelectric conversion efficiency of perovskite solar cells is improved, reaching 24.4%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462742A_ABST
    Figure CN119462742A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic photoelectric materials, and particularly discloses a multifunctional organic semiconductor material with cyano phosphonic acid as an anchoring group and a preparation method and application of the multifunctional organic semiconductor material. The cyano group in the anchoring group can effectively increase the deprotonation capability of phosphonic acid and enhance the hydrophilicity of the anchoring group, so that the material has unique amphiphilic characteristics and shows good wettability, and further, the high-quality perovskite thin film is obtained. Meanwhile, F atoms in the arylamine enhance the interface interaction between the hole transport layer and the perovskite layer, thereby further regulating the crystallization of the perovskite, passivating the bottom interface defect of the perovskite, and inhibiting the non-radiative recombination of the interface. The organic semiconductor material is highly conjugated in molecules and good in photo-thermal stability. When the hole transport layer is applied to a trans-perovskite solar cell, the photoelectric conversion efficiency of more than 24.5% can be obtained, and the hole transport layer shows a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells and relates to the preparation of organic semiconductor materials, in particular to an organic semiconductor material based on a pyrene core self-assembled monomolecular layer and a preparation method and application thereof. Background Art

[0002] As a new generation of photovoltaic technology, perovskite solar cells (PSCs) have the advantages of simple preparation process, easy material adjustment, and low cost. The latest certified efficiency has reached 26.7% (National Renewable Energy Laboratory, NREL, 2024). Compared with the traditional formal structure (nip) PSCs, the inverted structure (pin) PSCs have the advantages of low-temperature processing, compatibility with large-scale manufacturing, low hysteresis, and good stability. Therefore, it has considerable development prospects in the field of perovskite photovoltaics in the future. At present, the hole transport material (HTMs) poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA) hole transport layer commonly used in trans devices has poor wettability of perovskite solution on its surface, resulting in poor film quality and high interface defect state density. These problems limit its further performance improvement and commercial application. For this reason, the development of high-performance, new trans devices for hole transport materials is crucial to the performance of the device.

[0003] In recent years, self-assembled monolayers (SAMs) as hole transport materials have the characteristics of simple structure and flexible design. They can effectively adjust the interface energy level and reduce defect states based on molecular engineering. SAMs-type hole transport layers can be tightly bonded to the substrate through chemical bonds and have high stability. At the same time, the monolayer has a minimum layer thickness, which is also conducive to reducing parasitic absorption and improving the upper limit of device efficiency. Therefore, the development of new SAM materials with simple structure, low cost and excellent performance is a key issue that needs to be solved to promote the industrialization of PSCs. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an organic semiconductor material based on a pyrene core self-assembled monolayer. The semiconductor material provided by the present invention uses phosphoric acid as an anchoring group, a benzene ring as a connecting unit, and pyrene as a main core to replace traditional carbazole or thiophene and its derivatives as the main core. The pyrene core has better planarity than the traditional carbazole main core, which is conducive to better energy level matching. Using it as a hole transport layer can improve the high hole mobility and hole extraction ability. The SAMs material is scalable, dopant-free, simple to handle and cheap. Another purpose of the present invention is to provide a preparation method of the organic semiconductor material based on the pyrene core self-assembled monolayer.

[0005] The present invention is achieved through the following technical solutions:

[0006] An organic semiconductor material based on a pyrene core self-assembled monolayer, the chemical structure of which is shown below:

[0007]

[0008] A further improvement of the present invention is:

[0009] A method for preparing an organic semiconductor material based on a pyrene core self-assembled monolayer comprises the following steps:

[0010] S1: Compound 1 undergoes a coupling reaction with bromobenzoyl chloride to generate intermediate 2;

[0011]

[0012] S2: subjecting intermediate 2 to reduction reaction to generate intermediate 3;

[0013]

[0014] S3: Substitution reaction of intermediate 3 with diethyl phosphite to generate intermediate 4;

[0015]

[0016] S4: hydrolyzing the intermediate 4 to generate the target product, i.e., a self-assembled monolayer;

[0017]

[0018] Furthermore, in S1, under an argon atmosphere, compound 1 and bromobenzoyl chloride are mixed in anhydrous dichloromethane, the mixed solution is cooled to 0°C, and aluminum chloride is slowly added to cause a substitution reaction to generate compound 2, wherein the molar ratio of compound 1, bromobenzoyl chloride and aluminum chloride is 1:1-2:1-5.

[0019] Furthermore, in S2, under an argon atmosphere, compound 2 and sodium borohydride are mixed and dissolved in tetrahydrofuran, and aluminum chloride is added in batches at room temperature to cause a reduction reaction to generate compound 3, wherein the molar ratio of compound 2, sodium borohydride and aluminum chloride is 1:2-10:2-10.

[0020] Furthermore, in S3, compound 3, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate and diethyl phosphite are dissolved in 1,4-dioxane, and a substitution reaction occurs under an argon atmosphere to generate compound 3, wherein the molar ratio of compound 3, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate and diethyl phosphite is 1:0.05-0.1:0.01-0.1:5-10:5-40.

[0021] Furthermore, in S4, compound 4 and bromotrimethylsilane are dissolved in 1,4-dioxane, and a hydrolysis reaction is carried out under an argon atmosphere to obtain the target product WZ4; the molar ratio of compound 4 to bromotrimethylsilane is 1:5-10.

[0022] Further, in S1, the substitution reaction is carried out at room temperature, and the reaction time is 6 to 12 hours;

[0023] And / or, in S2, the reduction reaction temperature is 50-100° C. and the time is 1-2 h;

[0024] And / or, in S3, the substitution reaction temperature is 100-170°C and the time is 10-20h;

[0025] And / or, in S4, the hydrolysis reaction is carried out at room temperature for 10 to 24 hours.

[0026] A further improvement of the present invention is:

[0027] The above-mentioned application of pyrene core self-assembled monolayer organic semiconductor materials in perovskite solar cells.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention provides an organic semiconductor material based on a pyrene core self-assembled monolayer, a preparation method and an application thereof, with pyrene as the main core, phosphoric acid as the anchoring group, and a benzene ring as a connecting unit. Pyrene has a larger conjugated planar structure, which induces stronger intermolecular interactions and promotes the molecules to form a more ordered and compact SAM on an ITO substrate; at the same time, the aromatic ring acts as a connecting group to promote the formation of a dense self-assembled monolayer film and enhance hole extraction and transmission performance.

[0030] 2. The self-assembled monolayer organic semiconductor material provided by the present invention is used as a hole transport layer in perovskite solar cells. The test results show that the short-circuit photocurrent density of the battery device reaches 25.58mAcm-2, the open-circuit voltage is 1.14V, the fill factor is 0.8358, and the photoelectric conversion efficiency reaches 24.4%, which has practical significance for improving the efficiency of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The NMR spectrum of formula WZ4 prepared by the present invention;

[0032] Figure 2 The JV curve of the inverse perovskite solar cell prepared by using the WZ4 prepared in the present invention as a self-assembled monolayer. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with specific embodiments.

[0034] The invention provides a synthesis process of a pyrene core self-assembled monomolecular layer organic semiconductor material WZ4.

[0035]

[0036] The synthetic route is as follows:

[0037]

[0038] Example 1: Synthesis of WZ4

[0039] (1) Synthesis of compound of formula 2:

[0040] Under argon protection, raw material 1 (1.8 g, 9 mmol) and bromobenzoyl chloride (1.99 g, 9.06 mmol) were added to a 100 mL single-mouth round-bottom flask in turn and dissolved in anhydrous dichloromethane (10 mL). The mixed solution was cooled to 0°C, and aluminum chloride (1.18 g, 9 mmol) was slowly added to the mixed solution in batches, and reacted at room temperature for 10 h. The mixture was slowly poured into ice water, 1-2 drops of concentrated hydrochloric acid were added, and the mixture was extracted with dichloromethane. The organic phase was distilled under reduced pressure, and the crude product was passed through a chromatography column (eluent: petroleum ether / dichloromethane = 50 / 1 to 5 / 1) to obtain 1.89 g of the compound shown in formula 2 as a yellow-green solid with a yield of 55%.

[0041] The structural characterization data of the compound of formula 2 are: 1 HNMR(400MHz,Chloroform-d)δ8.33(d,J=9.3Hz,1H),8.26(m,2H),8.22–8.19(m,2H), 8.15–8.09(m,2H),8.06(dd,J=7.8,5.0Hz,2H),7.78–7.74(m,2H),7.66–7.60(m,2H).

[0042] (2) Synthesis of the compound of formula 3:

[0043] Under argon protection, raw material 2 (1.89 g, 5 mmol) and sodium borohydride (0.92 g, 24.3 mmol) were added to a 100 mL single-mouth round-bottom flask in turn and dissolved in anhydrous tetrahydrofuran (15 mL). Aluminum chloride (1.31 g, 9.8 mmol) was slowly added to the mixture in batches at room temperature, and the mixture was reacted at 70°C for 1.5 h. The mixture was slowly poured into ice water, extracted with dichloromethane, and the organic phase was distilled under reduced pressure. The crude product was passed through a chromatography column (eluent: petroleum ether / ethyl acetate = 50 / 1 to 10 / 1) to obtain 1.32 g of the compound shown in formula 3 as a light yellow solid with a yield of 76%.

[0044] The structural characterization data of the compound of formula 3 are: 1 H NMR(400MHz,Chloroform-d)δ8.22–8.12(m,4H),8.08–8.04(m,3H),8.00(t,J=7.6Hz, 1H),7.85(d,J=7.8Hz,1H),7.37(d,J=8.4Hz,2H),7.07(d,J=8.4Hz,2H),4.68(s,2H).

[0045] (3) Synthesis of compound of formula 4:

[0046] Under argon protection, intermediate 3 (1.32 g, 3.6 mmol) and diethyl phosphite (9.82 g, 71 mmol), palladium acetate (90 mg, 0.36 mmol), 1,1'-bis(diphenylphosphino)ferrocene (19 mg, 0.04 mmol), potassium acetate (2.1 g, 21 mmol) and 1,4-dioxane (10 mL) were added to a 100 mL double-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, it was extracted with dichloromethane, and the excess diethyl phosphite was distilled off under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 1.09 g of intermediate 4 as a white solid with a yield of 72%.

[0047] (4) Synthesis of formula WZ4:

[0048] Under argon protection, intermediate 3 (1.09 g, 2.6 mmol), trimethylsilyl bromide (3.9 g, 26 mmol) and 10 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 24 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was recrystallized from methanol and water to obtain 0.52 g of a white solid with a yield of 55%.

[0049] The structural characterization data of the compound of formula WZ4 are:1 H NMR (400MHz, DMSO-d6) δ8.34(d,J=9.3Hz,1H),8.27(m,3H),8.20–8.15(m,3H),8.09–8.00(m,2H),7.57(m,2H),7.34(dd,J=8.1,3.3Hz,2H).

[0050] Example 2: Synthesis of WZ4

[0051] (1) Synthesis of compound of formula 2:

[0052] Under argon protection, raw material 1 (1.8 g, 9 mmol) and bromobenzoyl chloride (1.99 g, 9.06 mmol) were added to a 100 mL single-mouth round-bottom flask in turn and dissolved in anhydrous dichloromethane (10 mL). The mixed solution was cooled to 0°C, and aluminum chloride (1.73 g, 12.9 mmol) was slowly added to the mixed solution in batches, and reacted at room temperature for 10 h. The mixture was slowly poured into ice water, 1-2 drops of concentrated hydrochloric acid were added, and the mixture was extracted with dichloromethane. The organic phase was distilled under reduced pressure, and the crude product was passed through a chromatography column (eluent: petroleum ether / dichloromethane = 50 / 1 to 5 / 1) to obtain 2.06 g of the compound shown in formula 2, a yellow-green solid, with a yield of 60%.

[0053] (2) Synthesis of the compound of formula 3:

[0054] Under argon protection, raw material 2 (2.06 g, 5 mmol) and sodium borohydride (1 g, 26.4 mmol) were added to a 100 mL single-mouth round-bottom flask in turn and dissolved in anhydrous tetrahydrofuran (15 mL). Aluminum chloride (3.56 g, 26.7 mmol) was slowly added to the mixture in batches at room temperature, and the mixture was reacted at 70°C for 1.5 h. The mixture was slowly poured into ice water, extracted with dichloromethane, and the organic phase was distilled under reduced pressure. The crude product was passed through a chromatography column (eluent: petroleum ether / ethyl acetate = 50 / 1 to 10 / 1) to obtain 1.59 g of the compound shown in formula 3 as a light yellow solid with a yield of 80%.

[0055] (3) Synthesis of compound of formula 4:

[0056] Under argon protection, intermediate 3 (1.59 g, 4 mmol) and diethyl phosphite (11.83 g, 86 mmol), palladium acetate (100 mg, 0.4 mmol), 1,1'-bis(diphenylphosphino)ferrocene (69 mg, 0.13 mmol), potassium acetate (2.25 g, 25.7 mmol) and 1,4-dioxane (10 mL) were added to a 100 mL double-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, it was extracted with dichloromethane, and the excess diethyl phosphite was distilled off under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 1.47 g of intermediate 4 as a white solid with a yield of 80%.

[0057] (4) Synthesis of formula WZ4:

[0058] Under argon protection, intermediate 3 (1.47 g, 3 mmol), trimethylsilyl bromide (4.2 g, 27.5 mmol) and 10 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 24 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was recrystallized from methanol and water to obtain 0.77 g of a white solid with a yield of 60%.

[0059] Example 3: Characterization and performance verification

[0060] The self-assembled monolayer hole transport material WZ4 prepared in Example 1 has a nuclear magnetic resonance spectrum as shown in Figure 1 shown.

[0061] This embodiment provides an inverted perovskite solar cell prepared by using the formula WZ4 prepared in Example 1 as a self-assembled monolayer, and the perovskite solar cell is prepared according to the method disclosed in the literature: G.Qu; S.Cai; Y.Qiao; et al.Joule, 2024, 8, 2123-2134. Test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), data acquisition using Keithley 2400 digital source meter. Test results are shown in Figure 2 The short-circuit photocurrent density of the battery device reached 25.58 mA cm -2 , the open circuit voltage is 1.14V, the fill factor is 0.8358, and the photoelectric conversion efficiency reaches 24.4%.

[0062] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An organic semiconductor material based on pyrene core self-assembled monolayer, characterized in that: The chemical structure is shown below:

2. The method for preparing an organic semiconductor material based on a pyrene core self-assembled monolayer as claimed in claim 1, characterized in that: The following steps are involved: S1: Compound 1 undergoes a coupling reaction with bromobenzoyl chloride to generate intermediate 2; S2: subjecting intermediate 2 to reduction reaction to generate intermediate 3; S3: Substitution reaction of intermediate 3 with diethyl phosphite to generate intermediate 4; S4: hydrolyzing the intermediate 4 to generate the target product, i.e., a self-assembled monolayer; 3. The method for preparing an organic semiconductor material based on a pyrene core self-assembled monolayer according to claim 2, characterized in that: In S1, under an argon atmosphere, compound 1 and bromobenzoyl chloride are mixed in anhydrous dichloromethane, and the mixed solution is cooled to 0°C and then aluminum chloride is slowly added to generate compound 2 by substitution reaction, wherein the molar ratio of compound 1, bromobenzoyl chloride and aluminum chloride is 1:1-2:1-5.

4. The method for preparing an organic semiconductor material based on a pyrene core self-assembled monolayer according to claim 2, characterized in that: In S2, under an argon atmosphere, compound 2 and sodium borohydride are mixed and dissolved in tetrahydrofuran, and aluminum chloride is added in batches at room temperature to cause a reduction reaction to generate compound 3, wherein the molar ratio of compound 2, sodium borohydride and aluminum chloride is 1:2-10:2-10.

5. The method for preparing an organic semiconductor material based on a pyrene core self-assembled monolayer according to claim 2, characterized in that: In S3, compound 3, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate and diethyl phosphite are dissolved in 1,4-dioxane, and a substitution reaction occurs under an argon atmosphere to generate compound 3, wherein the molar ratio of compound 3, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate and diethyl phosphite is 1:0.05-0.1:0.01-0.1:5-10:5-40.

6. The method for preparing an organic semiconductor material based on a pyrene core self-assembled monolayer according to claim 2, characterized in that: In S4, compound 4 and bromotrimethylsilane are dissolved in 1,4-dioxane, and a hydrolysis reaction is carried out under an argon atmosphere to obtain the target product WZ4; the molar ratio of compound 4 to bromotrimethylsilane is 1:5-10.

7. The method for preparing an organic semiconductor material based on a pyrene core self-assembled monolayer according to claim 2, characterized in that: In S1, the substitution reaction is carried out at room temperature for 6 to 12 hours; And / or, in S2, the reduction reaction temperature is 50-100° C. and the time is 1-2 h; And / or, in S3, the substitution reaction temperature is 100-170°C and the time is 10-20h; And / or, in S4, the hydrolysis reaction is carried out at room temperature for 10 to 24 hours.

8. Application of the organic semiconductor material based on pyrene core self-assembled monolayer as claimed in claim 1 in perovskite solar cells.

Citation Information

Cited By

  • Pyrene-carbazole-based diphosphonic acid self-assembled monomolecular material as well as preparation method and application thereof

    CN120590438A

  • Perovskite solar cell, laminated cell and photovoltaic module

    CN121531887A